2010
DOI: 10.1590/s0066-782x2010000600018
|View full text |Cite
|
Sign up to set email alerts
|

O transplante cardíaco biatrial deve ainda ser realizado? Metanálise

Abstract: .standard, two other techniques -the total and bicaval transplantation, were developed with the aim of ensuring better anatomical and physiological graft adaptation and better postoperative outcomes [5][6][7][8][9] . In fact, there are evidences in the literature that better results are obtained with the two techniques described more recently [10][11][12][13][14][15][16][17][18][19][20][21] . However, these evidences are weak when considered alone, and thus do not ensure an adequate level of evidence, especial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
13
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 47 publications
0
13
0
Order By: Relevance
“…Some studies reported a higher mortality rate with BA-HTX,8,9 whereas other publications found no difference 5,20,21…”
Section: Discussionmentioning
confidence: 96%
See 3 more Smart Citations
“…Some studies reported a higher mortality rate with BA-HTX,8,9 whereas other publications found no difference 5,20,21…”
Section: Discussionmentioning
confidence: 96%
“…In contrast, BC-HTX and TO-HTX preserved the geometry and conduction system of the right donor atrium, as well as these keep most of the left donor atrium intact 4,5. Consequently, a lower incidence of atrial arrhythmias compared to BA-HTX has been observed 8. However, differences in size of the left atrial diameter and the remaining left atrial tissue between the two previously mentioned techniques still exist.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This is in accordance with recent literature that has reported a higher rate of TR in biatrial implantation technique. 42 - 44 Sun et al 43 showed a significant higher rate of TR in patients with biatrial technique, and Goerler et al 5 reported that all but 1 case with tricuspid surgery occurred in patients transplanted in biatrial technique.…”
Section: Discussionmentioning
confidence: 99%